Technical Note: A custom‐designed flexible MR coil array for spine radiotherapy treatment planning. Issue 7 (11th May 2020) - Tyagi, Neelam; Zakian, Kristen L.; Italiaander, Michel; Almujayyaz, Salam; Lis, Eric; Yamada, Josh; Topf, Jill; Hunt, Margie; Deasy, Joseph O.
Abstract : Purpose: To assess the performance and optimize the MR image quality when using a custom‐built flexible radiofrequency (RF) spine coil array fitted between the immobilization device and the patient for spine radiotherapy treatment planning. Methods: A 32 channel flexible custom‐designed receive‐only coil array has been developed for spine radiotherapy simulation for a 3 T Philips MR scanner. Coil signal‐to‐noise performance and interactions with standard vendor hardware were assessed. In four volunteers, immobilization molds were created with a dummy version of the array within the mold, and subjects were scanned using the custom array in the mold. Phantoms and normal volunteers were scanned with both the custom spine coil array and the vendor's FDA‐approved in‐table posterior coil array to compare performance. Results: The superior–inferior field of view for the custom spine array was ~30 cm encompassing at least 10 vertebrae. A noise correlation matrix showed at least 25 dB isolation between all coil elements. Signal‐to‐noise ratio (SNR) calculated on a phantom scan at the depth of the spinal cord was a factor of 3 higher with the form‐fit spine array as compared to the vendor's posterior coil array. The body coil B1 transmit map was equivalent with and without the spine array in place demonstrating that the elements are decoupled from the body coil. Volunteer imaging showed improved SNR as compared to the vendor's posterior coil array. The custom array permitted a high degree of acceleration making possible the acquisition of isotropic high‐resolution 1.1 × 1.1 × 1.1 mm 3 three‐dimensional data set over a 30‐cm section of the spine in less than 5 min. Conclusion: The custom‐designed form‐fitting flexible spine coil array provided enhanced SNR and increased acceleration compared to the vendor's posterior array. Future studies will assess MR‐based spinal cord imaging with the custom coil in comparison to CT myelogram.